Aggressive primary cutaneous B‐cell lymphomas show increased Angiopoietin‐2‐induced angiogenesis. Issue 6 (16th April 2015) - Teichert, Martin; Stumpf, Christine; Booken, Nina; Wobser, Marion; Nashan, Dorothee; Hallermann, Christian; Mogler, Carolin; Müller, Cornelia S. L.; Becker, Jürgen C.; Moritz, Rose K. C.; Andrulis, Mindaugas; Nicolay, Jan P.; et al.
Abstract Primary cutaneous large B‐cell lymphomas, leg type (PCLBCL/LT) are primary cutaneous B‐cell lymphoma (PCBCL) with an intermediate prognosis. Therefore, antracycline‐based polychemotherapy combined with rituximab has been recommended as first‐line treatment. Yet, despite this regimen, the 5‐year survival rate remains 50–66% only. Angiogenesis, the formation of a vascular network, is essential for the pathogenesis of nodal lymphomas. So far, no study has analysed angiogenesis and its key factors in PCLBCL/LT. The present study was aimed at characterizing angiogenesis in PCLBCL/LT to identify the angiogenic molecules as potential therapeutic targets. The intra‐tumoral microvessel density (MVD) was assessed by immunohistochemical studies of CD20 and CD31. The MVD was higher in PCLBCL/LT compared with indolent PCBCL. Analyses of open‐source microarray data showed correlation between the angiogenic molecule angiopoietin‐2 (Ang‐2) and pan‐endothelial cell markers. ELISA studies determined a shift between Ang‐2 and Ang‐1 towards Ang‐2 in the peripheral blood of PCLBCL/LT patients. Immunofluorescence costainings against the Ang receptor Tie2/angiogenic integrins/CD34 revealed that the vasculature in both aggressive and indolent PCBCL tumors harbours an endothelial cell subpopulation with reduced expression of Tie2. In contrast, the alternative Ang‐2 binding partners, angiogenic integrins, are strongly expressed in PCBCL. In line with these findings, downstream targets of Ang‐2‐integrin signalling, that is phosphorylation of focal adhesion kinase at Tyr397, and sprouting angiogenesis are enhanced in PCLBCL/LT. Our data present Ang‐2 as a promising therapeutic target and anti‐angiogenic therapy as a new line in treatment of PCLBCL/LT as a hitherto intractable disease.